Using crashed bricks to increase the thermal resistance of building roofs in hot countries - Husseini, Marwah Dawoud (Journal of engineering sciences and information technology, 2022)
In hot countries like Iraq, during the summer season, the temperature reaches about 50 °C, which has a direct impact on energy consumption due to the usage of cooling systems. Therefore, this study aims to reduce the solar radiation that is absorbed by the building’s roof by using an insulator made of crashed bricks. In this research, a small model was created to replicate the roof properties, and then a heater set at the appropriate temperature was used to mimic the amount of heat coming from the sun. The amount of heat transfer is calculated for the roof with and without the insulator, and the study determines the different thicknesses and sizes of crashed brick as an insulator.
Keywords: building roof; crashed bricks; energy storage; heat transfer